2016
DOI: 10.1530/jme-15-0257
|View full text |Cite
|
Sign up to set email alerts
|

60 YEARS OF POMC: Adrenal and extra-adrenal functions of ACTH

Abstract: The pituitary adrenocorticotropic hormone (ACTH) plays a pivotal role in homeostasis and stress response and is thus the major component of the hypothalamo–pituitary–adrenal axis. After a brief summary of ACTH production from proopiomelanocortin (POMC) and on ACTH receptor properties, the first part of the review covers the role of ACTH in steroidogenesis and steroid secretion. We highlight the mechanisms explaining the differential acute vs chronic effects of ACTH on aldosterone and glucocorticoid secretion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 230 publications
(227 reference statements)
2
54
0
Order By: Relevance
“…Several effects of ACTH in adrenal cells are mediated by the activation of the cAMP/PKA pathway (Kimura 1986, Schimmer 1995, Gallo-Payet & Payet 2003, Sabban et al 2004, Gallo-Payet 2016. As stated previously, among them we have demonstrated the participation of the cAMP/PKA pathway in the transcriptional stimulation of HO-1 by ACTH (Pomeraniec et al 2004).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several effects of ACTH in adrenal cells are mediated by the activation of the cAMP/PKA pathway (Kimura 1986, Schimmer 1995, Gallo-Payet & Payet 2003, Sabban et al 2004, Gallo-Payet 2016. As stated previously, among them we have demonstrated the participation of the cAMP/PKA pathway in the transcriptional stimulation of HO-1 by ACTH (Pomeraniec et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…Role of CREB on heme oxygenase-1 induction in adrenal cells: involvement of the PI3K pathway pathway (Gallo-Payet 2016). In turn, stimulation of PKA activity is involved in the phosphorylation and activation of several transcription factors engaged in the transcriptional stimulation of steroidogenic-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Its exact mechanism is not entirely understood: it is suggested that increased concentrations of cortisol in the adrenal cortex directly inactivates the last steps of aldosterone synthesis in the ZG (27); there is also evidence that initial ZG cells undergo a differentiation process toward cortisol producing cells (28). …”
Section: Chronic Acth Excess In Man and Corticosteroid Secretionmentioning
confidence: 99%
“…The exact mechanism whereby ACTH promotes adrenocortical growth still is complex and remains partially understood, since in vitro studies show a paradoxical negative effect of ACTH on adrenocortical cell proliferation (36) The growth-stimulatory effect of ACTH in vivo most likely proceeds through the activation of a local and complex network of autocrine growth factors and their own receptors; a number substances, including non-ACTH POMC peptides such as γ3-MSH, have been shown to exert some adrenocortical growth effect (28). …”
Section: Chronic Acth Excess In Man and Adrenal Cortex Growthmentioning
confidence: 99%
“…Aldosterone thus plays a central role in the regulation of blood pressure mainly by acting on the distal tubules and collecting ducts of the nephron. To a lesser extent, the adrenocorticotropic hormone (ACTH) also stimulates the secretion of aldosterone from adrenals (Gallo-Payet 2016). In healthy adults, the adrenal cortex produces 20-200 µg of aldosterone per day.…”
Section: :10mentioning
confidence: 99%